Origin, evolution, and sedimentary records of islands in large anabranching tropical rivers: The case of the Upper Paraná River, Brazil - Leli, Isabel T. [UNESP]; Stevaux, José C.; Assine, Mario L. [UNESP] (Elsevier, 2020)
Anabranching patterns are characteristic of the largest rivers in the world. We have chosen to study the Paraná River because of its worldwide importance among the great rivers and the large database available from over four decades of research. In this paper, we present results on the classification, origin, evolutionary processes, and sedimentary records of islands that form anabranching patterns in the Upper Paraná River in Brazil. These islands are formed by in-channel processes that drive their evolution from central bar islands and by off-channel processes that form floodplain-excised island. Both types of islands can increase in area by the annexation of lateral bars, forming composite islands. The islands formed by floodplain excision are normally larger than the other types, with ages of up to 14.6 ka. The sedimentary records of these islands are relatively simple. Central bar islands present a lower lithosome comprising sandy channel deposits (Sp, St, Sm, and Sm(o) facies) that correspond to central and lateral bar formation, followed by a mud sequence (Fm, Fl, and Fm(o) facies) deposited by vertical accretion events during flood stages. Floodplain-excised islands have the same sedimentary sequence as the floodplain from which they were detached. The in-channel island-forming processes described in this paper may have been operating since the beginning of the Holocene. The understanding of island origin and evolution processes presented in this paper is fundamental to ecological and geomorphological studies, as in the sustainable management of large anabranching rivers.
Keywords: Anabranching pattern; Fluvial facies analysis; Fluvial island; Multichannel river; Paraná River; Tropical River